Cloud cryptography: a new approach with distributed storage - Agarwal, Rakshanda; Regunathan, Rajeshkannan (International Journal of Engineering and Technology, 2018)
With the evolution of cloud computing, there is an astounding need of security solutions. Some of the primary considerations here is brought on by inappropriate warehousing of data. This particular consideration significantly enhances users' anxiousness and minimizes the adoptability of cloud computing in numerous areas, including the financial industry and governmental agencies. The most effective method to offer risk-free data transfer is via cloud cryptography and storage techniques. Considering this, we propose a new and more secure algo-rithm for the transmission of data over the cloud. In this algorithm, the data is encrypted and then split into two different parts. Each part is stored in a different cloud. This makes the data challenging for being accessed by any type of hacker, even when accessed it will be of no use to him. This will use three encryption and two decryption keys, hence a combination of symmetric and asymmetric cryptography.Â Â